2021
DOI: 10.3389/fsufs.2021.769094
|View full text |Cite
|
Sign up to set email alerts
|

Does Information Acquisition Influence the Adoption of Sustainable Land Management Practices? Evidence From Mpumalanga Province South Africa

Abstract: Agricultural information plays a vital role in adopting agricultural technology. The study explored if information acquisition is related to the adoption of sustainable land management practices (SLMP) and jointly decided in Mpumalanga Province of South Africa. Primary data were collected through face-to-face interviews, using a proportionate random sampling technique to get 250 smallholder farmers to participate in the survey. A seemingly unrelated bivariate probit (SUBP) model and a recursive bivariate probi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The probable justification is that the provision of extension services improves the awareness of farmers and reduces the primitive way of soil conservation practices. This result is congruent with the findings of Oduniyi and Tekana (2021). Sex of household head: In most developing countries gender differences are significant.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The probable justification is that the provision of extension services improves the awareness of farmers and reduces the primitive way of soil conservation practices. This result is congruent with the findings of Oduniyi and Tekana (2021). Sex of household head: In most developing countries gender differences are significant.…”
Section: Resultssupporting
confidence: 90%
“…There are several studies conducted to show the linkage between access to agricultural extension services and the adoption of sustainable soil conservation practices. Oduniyi and Tekana (2021) analyzed the linkage between information acquisition and the adoption of sustainable land management practices (SLMP) and found that the years spent in school; agricultural extension service; the number of extension visits and the years of farming, influenced both information acquisition and the adoption of soil conservation practices.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Sandee and Rietveld [12] argue that technology adoption is not solely determined by costs and the level of benefits gained from innovation adoption, but that access to technological information also plays a crucial role. Farmers' decision to adopt new technological practices is preceded by the information received or acquired about the introduced technology [13]. Research findings indicate a significant correlation between access to media and group interaction and farmers' adoption levels.…”
Section: Determinants Factor Of Technology Adoptionmentioning
confidence: 97%
“…There are several studies conducted to show the linkage between access to agricultural extension services and the adoption of sustainable soil conservation practices. Oduniyi and Tekana (2021) analyzed the linkage between information acquisition and the adoption of sustainable land management practices (SLMP) and found that the years spent in school; agricultural extension service; the number of extension visits and the years of farming, in uenced both information acquisition and the adoption of soil conservation practices.…”
Section: Empirical Literaturementioning
confidence: 99%